A meta-analysis of the value of circulating tumor cells in monitoring postoperative recurrence and metastasis of colorectal cancer - Wu, Jiao; Li, Zhongyu; Zou, Jianhua; Li, Liusheng; Cui, Ning; Hao, Tengteng; Yi, Kangjun; Yang, Jingyan; Wu, Yu (PloS one, 2022)
Circulating tumor cells (CTCs) as novel biomarkers are widely investigated in various cancers, although most of the literature shows that CTCs have predictive value for recurrence, metastasis, and prognosis after CRC surgery, results remain controversial. We aimed to systematically evaluate the value of CTCs in monitoring of colorectal cancer (CRC) recurrence and metastasis after surgery. The PubMed, Cochrane Library, Embase, and other databases were searched from the establishment of the database to May 27, 2021. Relevant literature searches and data extraction were performed independently by two reviewers. The quality assessment was performed using the QUADAS2 scale developed by the Cochrane collaboration. The heterogeneity was checked using the Spearman correlation coefficient and the Cochran-Q test in the Meta-Disc1.4 software. Subgroup analysis was used to explore the source of heterogeneity. Considering that all the included papers were clinical studies with clinical heterogeneity, random effect model was adopted for analysis. And the sensitivity (Sen), specificity (Spe), positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and summary receiver operating characteristic (SROC) curves of CTCs, in monitoring recurrence and metastasis after CRC, were calculated. The publication bias of the included studies was assessed using Deek's funnel figure. The literature included a total of 13 articles, comprising 1788 cases, and the overall quality of the literature was high. After summing up the indicators, the sensitivity pooled-value of the peripheral blood CTCs to monitor the recurrence and metastasis value of CRC after CRC was 0.67 [95%CI (0.62, 0.71)], specificity pooled-value was 0.71 [95%CI (0.67, 0.72)], PLR pooled-value was 2.37 [95%CI [1.52, 3.71]), NLR pooled into 0.53 [95%CI (0.36, 0.78)], DOR pooled into 4.97 [95%CI (2.11, 11.72)], AUC was 0.7395. Peripheral blood CTCs have a moderate monitoring value for recurrence and metastasis after CRC; CTCs detected one week after surgery may be more correlated with recurrence and metastasis.